Hypogammaglobulinemia Observed One Year after Rituximab Treatment for Idiopathic Thrombocytopenic Purpura - Bilal Ahmad Shoukat; Osama Ali; Dileep Kumar; Muhammad Bilal Gilani; Adeela Zahid; Shaheer Aslam Joiya; Maqsood Anwar Malik (Case Reports in Medicine)
We present the case of a 19-year-old female with severe hypogammaglobulinemia after having had treatment with rituximab for idiopathic thrombocytopenic purpura requiring intravenous immunoglobulins. She was admitted with the diagnosis of left-sided pneumonia with parapneumonic effusion. The patient was treated with piperacillin/tazobactam after having a poor response to co-amoxiclav. The patient had been tested for immunoglobulin levels, and the levels were very low. She has a history of ITP for which she received steroids. She also received rituximab for the same on four separate occasions, and the last one was about 1 year ago.